Perancangan Kampanye Sosial Kampanye Sosial "Politik Gak Ribet!" Sebagai Media Literasi Dasar Politik Bagi Gen Z - Rizka Alya Hamzah; Nisa Putri Rachmadani; Alfikhairina Jamil (Meraki: Journal of Creative Industries, 2025)
The low political participation among first-time voters and the strong reliance of Generation Z on social media highlight the need for accessible political education. This study aims to design a social campaign titled “Politik Gak Ribet!” as a basic political literacy medium for Gen Z. The campaign integrates motion graphics as the primary medium with interactive zines as a supporting medium, utilizing a design thinking approach to ensure engaging and meaningful communication.The campaign addresses four key topics: the importance of collective goals through discussion, fundamental knowledge of the electoral system, the impact of social media on political opinion, and the issue of political apathy. Visual elements include folk-art-style children's illustrations, fable-based metaphors, and simple interactive games such as crosswords to foster emotional and cognitive engagement.The results of this design project indicate the potential of visually driven and interactive media to serve as alternative educational tools that resonate with young audiences. The campaign is expected to promote critical awareness and encourage active civic engagement among Gen Z in Indonesia’s political sphere.